Probenecid Pre-treatment Downregulates the Kidney Cl-/HCO3- Exchanger (Pendrin) and Potentiates Hydrochlorothiazide-Induced Diuresis - Barone, Sharon; Xu, Jie; Zahedi, Kamyar; Brooks, Marybeth; Soleimani, Manoocher (Frontiers in Physiology, 2018)
Background: Probenecid is a uricosuric agent that in addition to exerting a positive ionotropic effect in the heart, blocks the ATP transporter Pannexin 1 and inhibits the Cl-/HCO3- exchanger, pendrin. In the kidney, pendrin blunts the loss of salt wasting secondary to the inhibition of the thiazide-sensitive Na+-Cl- co-transporter (NCC/SLC12A3). Hypothesis: Pre-treatment with probenecid down-regulates pendrin; therefore, leaving NCC as the main salt absorbing transporter in the distal nephron, and hence enhances the hydrochlorothiazide (HCTZ)-induced diuresis. Methods: Daily balance studies, blood and urine chemical analysis, immunofluorescence, as well as western and northern blot analyses were utilized to examine the effects of probenecid alone (at 250 mg/kg/day) or in combination with HCTZ (at 40mg/kg/day) on kidney function and on salt and water transporters in the collecting duct. Results: Male Sprague Dawley rats were subjected to three different protocols: 1) HCTZ for 4 days, 2) probenecid for 10 days, and 3) primed with probenecid for 6 days followed by probenecid and HCTZ for 4 additional days. Treatment protocol 1 (HCTZ for 4 days) only mildly increased the urine volume (U Vol) from a baseline of 9.8 to 13.4ml/day. In response to treatment protocol 2 (probenecid for 10 days), U Vol increased to 15.9 ml/24 hrs. Treatment protocol 3 (probenecid for 6 days followed by probenecid and HCTZ for 4 additional days) increased the U Vol to 42.9 ml/day on day 4 of co-treatment with HCTZ and probenecid (compared to probenecid p=0.003, n=5 or HCTZ alone p=0.001, n = 5). Probenecid treatment at 250mg/kg/day downregulated the expression of pendrin and led to a decrease in AQP2 expression. Enhanced diuresis by probenecid plus HCTZ was not associated with volume depletion. Conclusion: Probenecid pre-treatment downregulates pendrin and robustly enhances diuresis by HCTZ-mediated NCC inhibition in kidney.